ChemInform Abstract: Cu‐Catalyzed Transformation of Alkynes and Alkenes with Azide and Dimethyl Sulfoxide Reagents. Issue 19 (April 2016) - Shen, Tao; Huang, Xiaoqiang; Liang, Yu‐Feng; Jiao, Ning
Abstract: as a facile route for the synthesis of 1‐((alkylthio)methyl)‐1H‐1, 2, 3‐triazoles